DYSLIPIDEMIA IN TYPE 2 DIABETES MELLITUS: MORE ATHEROGENIC LIPID PROFILE IN WOMEN - M. Nakhjavani; A. R. Esteghamati; F. Esfahanian A. R. Heshmat (Acta Medica Iranica, 2006)
Previous studies have shown that diabetes mellitus (DM) increases the risk of cardiovascular disease in women to a greater extent than in men. It seems that DM may alter lipid profiles more adversely in women compared to men. In this study we evaluated serum lipoprotein differences in type 2 diabetic men and women. The study included 350 type 2 diabetic patients (100 men and 250 women), aged 19-82 years. Demographic data were and biochemistry tests including serum lipoproteins were measured. There was no difference between men and women with respect to duration of DM and type of treatment. Body mass index (BMI), systolic and diastolic blood pressures were significantly higher in women than age matched men. Women also had significantly higher plasma levels of total cholesterol (233.7 vs. 190.3 mg/dl, P < 0.001), triglycerides (219.7 vs. 180.6 mg/dl, P < 0.05), lowdensity lipoprotein cholesterol (LDL-C) (141.2 vs. 116.1 mg/dl, P < 0.001), high-density lipoprotein cholesterol (HDL-C) (47.1 vs. 39.4 mg/dl, P < 0.001), non-HDL cholesterol (186.1 vs. 150.8 mg/dl, P